Damp‐heat induced degradation in photovoltaic modules manufactured with passivated emitter and rear contact solar cells. (11th March 2022) - Kyranaki, Nikoleta; Smith, Alex; Yendall, Keith; Hutt, David A.; Whalley, David C.; Gottschalg, Ralph; Betts, Thomas R.
Abstract: Corrosion is one of the main PV module failure mechanisms, as it can cause severe electrical performance degradation in PV modules exposed to hot and humid environments. Moisture penetrating a photovoltaic (PV) module may react with the metallic components causing corrosion. In addition, acetic acid which is produced by hydrolysis of ethylene vinyl acetate (EVA), the most common encapsulant, may further degrade metallic components. Corrosion is one of the main PV module failure mechanisms, as it can cause severe electrical performance degradation in PV modules exposed to hot and humid environments. The specific chemical reactions involved in the corrosion mechanisms for the different components are well understood. However, which of these causes the most serious degradation in the field, and therefore, most severe power loss is unknown. Moreover, the severity of corrosion in the absence of acetic acid is not yet well researched. This work distinguished between the front and rear side corrosion mechanisms and identified the different electrical signatures observed due to them. The experiment included damp‐heat (DH) conditioning of single‐cell mini‐modules, containing passivated emitter and rear contact (PERC) solar cells, laminated with a polyethylene terephthalate (PET) based backsheet. Furthermore, half‐encapsulated PERC PV cells were tested, with either the front or the rear side exposed. Electrical and material characterisation were conducted for the investigation of the sample degradation, and the performance decrease, related to the degradation of the rear surface passivation, was examined. Abstract : Single‐cell mini‐modules were aged under DH conditions. Their performance was compared with half‐encapsulated PV cells, either front or rear side exposed, for the identification of the relevant degradation mechanisms. All samples showed VOC reduction due to LeTID‐like mechanism, front side corrosion is a relevant PV module degradation mechanism, but not observed on the fully encapsulated mini‐modules studied here, and rear side corrosion is not relevant, as contensation of moisture is needed in order to observe Al contact decomposition.